PENGENALAN EKONOMI DAN BISNIS ISLAM MELALUI PENCEGAHAN PENYEBARAN VIRUS COVID-19 DI DESA CIMANGGU I, KECAMATAN CIBUNGBULANG, KABUPATEN BOGOR - Ermi Suryani; Bayu Purnama Putra; Muhamad Syahrulludin (Jurnal Pengabdian Kepada Masyarakat Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
Community service activities in 2020, in the Covid-19 pandemic situation that has hit the world, Indonesia is also experiencing the same impact where the government and society are trying to break the chain of spread and transmission of the Covid-19 virus. The Sahid Bogor Islamic Institute participates and contributes to efforts to deal with the problems of the Covid-19 pandemic, namely through community service. This community service was carried out in Cimanggu I Village, Cibungbulang District, Bogor Regency. At the same time, the introduction of Islamic Economics and Business was carried out